The use of informative-communication technologies is in organization of educational activity of students of tekhnologo-pedagogical specialities - Кучма, О. І.; Цись, О. О. (Pedagogy of Higher and Secondary Education, 2012)
Kuchma A. I., Tsys O. A. The use of informative-communication technologies is in organization of educational activity of students of tekhnologo-pedagogical specialities. Аrticle explains the specific of the use of informative-communication technologies in organization tekhnologo-pedagogical specialities students’ educational activity. The factors of improvement of students quality knowledges are considered at the study of technical disciplines with the use of informative-communication technologies, problems of introduction and use of the educational and controlling computer programs in an educational process and possible ways of their decision.